PENGARUH SITUATION-BASED LEARNING TERHADAP KEMAMPUAN CREATIVE PROBLEM SOLVING DAN SELF-EFFICACY SISWA - Fauziah, Mila Sri; Hanifah, Nurdinah; Isrok'atun, Isrok'atun (Jurnal Pena Ilmiah, 2019)
The background of this research based on Creative Problem Solving (CPS) skill and low student’s self-efficacy. Because CPS skill and student’s self-efficacy is very important, so it needs to step up. The solution to increase both of those goals, the researcher was chosen Situation Based Learning (SBL). This research method used quasi-experimental research with non-equivalent control group design. Sample of this research were students of SDN Karapyak I, which is VB class as the experimental class and VA class as the controlled class. The instrument of this research used CPS test, questionnaires, teacher’s performance observation sheet and student’s activities, and field notes. The results showed that SBL learning had a positive effect on CPS skill and student’s self-efficacy. SBL learning is better than conventional learning towards student’s CPS skill.Both of those learning give the same effect towards student’s self-efficacy , but it is not better effect. There is a positive relationship between CPS skill and student’s self-efficacy.